Red Sea Intermediate Water in the greater Agulhas Current system - Roman, Raymond Edward (Department of Oceanography, 2024)
Despite its small formation volume, Red Sea Intermediate Water (RSIW) has been observed as far south as the Agulhas Retroflection where it is involved in inter-ocean exchange. The spreading and contribution of RSIW has been established previously by combining all available hydrographic data. Considering the variable seasonal formation of RSIW and complex circulations patterns along its path south one would expect variable input of RSIW into the Agulhas Current system. Such variation in input cannot be established by combining all available data and can only be looked at using synoptic hydrographic sections. This is the aim of this thesis. To this aim a multi-parameter water mass analysis was used to establish the water mass content of RSIW along 36 hydrographic sections in the greater Agulhas Current system. In setting up the source water mass matrix a second question arose concerning the vertical spreading range of RSIW when North Indian Deep Water (NIDW), which is also defined as a oxygen poor water mass, was included in the source water matrix. Results showed the smallest input of RSIW comes from east of Madagascar. In terms of variability, the maximum RSIW contribution differed by more than a 100% between different sections at the southern tip of Madagascar. Although slightly smaller, this variability was also observed in the northern and southern mouth of the Mozambique Channel. Variability in the maximum RSIW contribution strongly correlated with the net transport of RSIW. This variability in the maximum water mass content and net transport of RSIW were observed as far south as the southern Agulhas Current. Differences in the transport and maximum contribution along the Agulhas Current were in some cases more than a 100%. It was thus concluded that the transport of RSIW along the Agulhas Current is highly variable making any estimates of transport for more than a singular hydrographic section impossible. In terms of the maximum density level, RSIW spreading appears in some cases to lie as deep as the ~crn=27.70 even when NIDW was introduced into the source water matrix. Although RSIW was detected as deep as the 27.7 surface, it was found that the bulk of the high salinity, low oxygen water was assigned as NIDW. In some cases all the high salinity, low oxygen water present was NIDW. We thus conclude that not all high salinity, low oxygen water in the south-west Indian Ocean is RSIW.